2001
DOI: 10.1093/ajcn/74.6.723
|View full text |Cite
|
Sign up to set email alerts
|

Plasma S -adenosylhomocysteine is a more sensitive indicator of cardiovascular disease than plasma homocysteine

Abstract: Plasma S-adenosylhomocysteine appears to be a much more sensitive indicator of the difference between patients with cardiovascular disease and control subjects than is homocysteine. Both plasma total homocysteine and S-adenosylhomocysteine are significantly correlated with plasma creatinine in patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
102
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(109 citation statements)
references
References 32 publications
6
102
1
Order By: Relevance
“…The results, shown in Table 1, were consistent with those in fresh control samples established in our laboratory 14 and with data from other laboratories, 9,12,[15][16][17][18] including studies that used specimens stored for several years. 10,19 The sole problem occurred with AdoHcy; our control sera produced abnormally high mean values and wide variations among samples.…”
Section: Laboratory Methodssupporting
confidence: 88%
See 1 more Smart Citation
“…The results, shown in Table 1, were consistent with those in fresh control samples established in our laboratory 14 and with data from other laboratories, 9,12,[15][16][17][18] including studies that used specimens stored for several years. 10,19 The sole problem occurred with AdoHcy; our control sera produced abnormally high mean values and wide variations among samples.…”
Section: Laboratory Methodssupporting
confidence: 88%
“…The difficulty of studying adequate numbers of patients with the relatively uncommon disease of pernicious anemia, especially the minority who have neurologic dysfunction, is exacerbated by the need to test them before they are treated and by the many exclusion criteria necessary for study of the issues they raise. Our resultant dependence on less than ideal specimens was partially addressed in several ways: (1) Results in control sera that were processed and stored like the test samples closely matched our 13 and others' reference ranges 9,12,[15][16][17][18] in freshly obtained samples; the sole exception was AdoHcy, which was therefore not included. (2) Experiments on sample-processing variations identified no relevant artifacts (see "Patients, materials, and methods").…”
Section: Transsulfuration and Related Thiol Metabolismmentioning
confidence: 99%
“…The relation between Hcy and hypomethylation has become a topic of utmost interest because the hypomethylation of many tissue components, including proteins, DNA, RNA, phospholipids, and small molecules, is one important mechanism by which Hcy may be cytotoxic [10]. In this respect a cause-control study showed that plasma AdoHcy concentration was a better predictor of cardiovascular diseases than plasma homocysteine [7].…”
Section: Introductionmentioning
confidence: 99%
“…The AHCY gene has been assigned to chromosome 20cen-q13.1 (Ensembl locus 20q11. 22) and consists of 10 exons spanning about 23 kb. Native human AHCY is a cytosolic protein composed of four identical subunits and requires NAD þ as a cofactor.…”
Section: Introductionmentioning
confidence: 99%